Ocorrência de enterotoxinas estafilocócicas em alimentos - Santos, Josiane Costa de Lima (2023)
Foodborne Diseases (FADs) pose a potential risk to consumer health and cause economic losses to the country, becoming a public health concern. According to the Notifiable Diseases Information System – SINAN, on average 700 DTA outbreaks are reported in Brazil per year and Staphylococcus aureus is among the three most relevant etiological agents. According to the legislation that provides microbiological parameters for foods (RDC 724/22 and IN 161/22), in addition to the analysis of coagulase-positive Staphylococci, the analysis of staphylococcal enterotoxin in three categories of food (milk and dairy products, dairy-based supplements and ready-to-eat foods), these being the ones that present the greatest risk for the presence of this toxin. This work aimed to evaluate food samples from the milk and dairy products categories, and dairy-based supplements, for the presence of staphylococcal enterotoxins, count of coagulase-positive Staphylococci strains and assessment of water activity. The 80 samples were collected at the retail market in the city of Campinas and analyzed at the Institute of Food Technology – ITAL, using Biomerieux's Vidas® SET2 detection kit. It was found that 8.75% of the samples showed a positive coagulase Staphylococcus count, ranging from 1x102 to 6,6x107 CFU/g and 2,5% of the analyzed samples showed a positive result for the presence of staphylococcal enterotoxin. A sample of artisanal Minas cheese with a count of 1x102 CFU/g, a value within the acceptable limit for coagulase-positive Staphylococci, showed a positive result for enterotoxin. A sample of melted dairy product where the presence of coagulase-positive Staphylococci was not detected also tested positive for staphylococcal enterotoxin. Both samples were within the water activity range (0,939 and 0,992 respectively) optimal for the production of enterotoxin. The incidence of enterotoxins in foods destined for the final consumer, although at a low percentage, indicates that the risk of contamination exists and it is necessary to control this toxin in these food categories.